Sportpreneurship as a Driver of Local Tourism Investment in The New World Era - Isyak Meirobie; Rizki Amelia; Valentina Happy Vanesa (Golden Ratio of Mapping Idea and Literature Format, 2026)
The transformation of tourism patterns in the post-pandemic era, following the global COVID-19 crisis, has encouraged the emergence of innovative sectors that integrate lifestyle, entrepreneurship, and tourism development. One emerging concept is sportpreneurship, which combines sports activities with entrepreneurial initiatives and tourism-based economic opportunities. This study aims to analyze the role of sportpreneurship in supporting sports tourism development, stimulating local investment, and contributing to regional economic growth in the new world era. This research employs a qualitative descriptive approach to explore the relationship between sportpreneurship, sports tourism development, and tourism-related investment. Data were collected through literature review, observation of sports tourism activities, and examination of investment developments in sports-based enterprises. The collected data were analyzed using descriptive and interpretative methods to understand the dynamics between sports entrepreneurship and tourism development. The findings indicate that sportpreneurship has become an important driver of tourism development by transforming sports activities into attractive tourism experiences. Sports events, recreational sports activities, and the development of sports facilities attract both domestic and international tourists while generating economic benefits for local communities. Furthermore, integrating sports and tourism creates new investment opportunities, particularly in sports infrastructure, tourism services, and recreational facilities. Overall, sportpreneurship contributes to tourism diversification, enhances destination attractiveness, and strengthens regional competitiveness. The study highlights that sportpreneurship can function as a catalyst for tourism investment and sustainable regional economic development. These findings provide insights for policymakers and tourism stakeholders on integrating sports-based entrepreneurship into tourism development strategies to support long-term economic growth and sustainable tourism.